Synthesis and characterization of a double oximato bridged dimeric copper(II) complex and its use in oxidative dimerisation of o-aminophenol. (1st January 2020) - Dutta, Tamal; Mirdya, Saikat; Giri, Pritam; Chattopadhyay, Shouvik
Graphical abstract: One new dinuclear copper(II) complex containing oxime-based tridentate Schiff base ligand has been synthesized and characterized. The catalytic ability of the complex in phenoxazinone synthase mimicking activity has been explored. Abstract: A dinuclear copper(II) complex, [(CH3 CN)Cu(L)2 Cu](ClO4 )2, has been synthesized by reacting an oxime-based tridentate Schiff base ligand, 3-[2-(dimethylamino)-ethylimino] butan-2-one oxime (HL ), with copper(II) perchlorate hexahydrate. The complex has been characterized by elemental and spectral analyses. Structure of the complex has been confirmed by single crystal X-ray diffraction technique. The complex may be used as moderate catalyst for the oxidation of o -aminophenol to 2-aminophenoxazine-3-one.